2022
DOI: 10.3390/separations9060137
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Steam Distillation Process and Chemical Constituents of Volatile Oil from Angelicaesinensis Radix

Abstract: In this study, the steam distillation process of volatile oil from Angelicae sinensis Radix was optimized according to the concept of quality-by-design. A homemade glass volatile oil extractor was used to achieve better cooling of the volatile oil. First, the soaking time, distillation time, and liquid–material ratio were identified as potential critical process parameters by consulting the literature. Then, the three parameters were investigated by single factor experiments. The volatile oil yield increased w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 9 publications
(13 reference statements)
1
1
0
Order By: Relevance
“…The oil obtained after the modifications had a Z-ligustilide content, the main component of this oil, that was higher than 85%, which indicates the high quality of the product obtained. The results of Wan et al [ 39 ], as well as those obtained in our study, support the idea that modifications to the process of obtaining essential oils can also result in an improved product quality.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The oil obtained after the modifications had a Z-ligustilide content, the main component of this oil, that was higher than 85%, which indicates the high quality of the product obtained. The results of Wan et al [ 39 ], as well as those obtained in our study, support the idea that modifications to the process of obtaining essential oils can also result in an improved product quality.…”
Section: Resultssupporting
confidence: 91%
“…The higher concentration found in the present experiments, when compared to those reported by Mahmoud et al [ 38 ], demonstrate that it is possible to perform extractions in an industrial manner that are of a higher quality than the laboratory-scale experiments. The study by Wan et al [ 39 ] proposed optimizations to the steam distillation process to obtain oil from Angelicae sinensis Radix with regard to the concept of quality by design. The oil obtained after the modifications had a Z-ligustilide content, the main component of this oil, that was higher than 85%, which indicates the high quality of the product obtained.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with some literature data reporting a 25-40% decrease in yield for some Cymbopogon EOs with increasing time [23]. Numerous studies have confirmed that EO yield decreases with time [24][25][26] or at least reaches equilibrium at some point without further increase [27][28][29]. There are also data from the literature suggesting different effects of drying on EO content [30], as some studies noted a significant decrease in yield [31], while others reported an increase [26].…”
Section: Eo Extractionsupporting
confidence: 90%